PROTEIN RECOMMENDATIONS FOR VEGETARIANS AND VEGANS: AN INTEGRATIVE REVIEW - Caldeira, Barbara; Antoniazzi dos Santos, Pâmela (Health and Society, 2024)
Objective: Analyze official protein recommendations for vegan and vegetarian individuals in all life stages. Methods: Integrative review carried out with official recommendations from six different countries and one continent, found in the PubMed database e Google Scholar. This study included articles with official recommendations from different countries, published in the last ten years in English, Spanish or Portuguese. Results: In the search, after analyzing the titles and abstracts, seven articles were considered for the study. Conclusions: Considering only proteins, it is possible to have a healthy vegetarian diet, provided that individuals are careful with protein consumption so that the daily recommendations are met and there is not any deficiency related to this macronutrient. However, in vegan diets, individuals should have greater caution since these only include plant protein sources which have lower bioavailability and, therefore, need to be consumed in a bigger quantity and from various different sources throughout the day. Nutritional assistance is essential in this dietary choice.